Ancestry analysis of locally adapted crespa goats from southernmost Brazil - Lopes, D.D.; Fernandez, G.P.; Poli, Mario Andres; Moreira, Gilson Rudinei Pires; Freitas, T.R.O.; Gonçalves, G.L. (2017)
Crespa goats are phenotypically similar to the Angora breed, and are traditionally reared in small, low-tech farms in southernmost Brazil. Whether they represent degenerated remnants of pure Angora goats or result from foreign breeds introduced during colonial times and recently mixed with commercial breeds is unknown. Since the degree of relatedness of Crespa in relation to other goats is completely unknown, we performed a comparative assessment of the genetic similarity between Crespa and foreign commercial breeds reared in the region (Angora, Alpine, Anglo-Nubian, Boer, and Saanen), particularly the Angora. We used 11 microsatellites to score alleles in 148 individuals and performed a Bayesian assignment test, which revealed six clusters (K = 6; Ln likelihood = -5047.6). In addition, a segment of the mitochondrial DNA (mtDNA) control region was sequenced to investigate the relatedness of Crespa goats to Portuguese autochthonous breeds (Algarvia, Bravia, Charnequeira, Serpentina, and Serrana). The origin of the Crespa breed could not be ascertained from the mtDNA, but it does not only descend from the Angora. It is probably related to other introduced and autochthonous Portuguese breeds, in particular the Algarvia. Therefore, our results indicate that this distinctive source of genetic diversity is partly a remnant of animals that were introduced during the colonial period. By recognizing it as genetically distinct, we provide further support for the protection of this particular gene pool.